Efficient one pot regioselective synthesis of a 3,3 `-spiro-phosphonylpyrazole-oxindole framework via base mediated [1,3]-dipolar cycloaddition reaction of the Bestmann-Ohira reagent with methyleneindolinones - Shelke, Anil M.; Suryavanshi, Gurunath (Organic & Biomolecular Chemistry, 2015)
A one pot, highly regioselective synthesis of racemic 3,3'-spiro-phosphonylpyrazole-oxindole by 1,3-dipolar cycloaddition of an in situ generated anion of dialkyl 1-diazomethylphosphonate from the Bestmann-Ohira reagent (BOR) & methyleneindolinones has been developed. The synthesis affords the highly functionalized pyrazole scaffolds in good yields with excellent regioselectivity under mild reaction conditions within a short reaction time.

Efficient organocatalytic route for asymmetric total synthesis of stagonolide F - Shelke, Anil M.; Suryavanshi, Gurunath (Tetrahedron Letters, 2015)
A stereoselective total synthesis of Stagonolide F (98% ee) is described employing asymmetric alpha-aminooxylation, Jorgensen's asymmetric epoxidation, Brown asymmetric allylation, Steglich esterification and ring closing metathesis as key steps. The use of organocatalytic alpha-aminooxylation and Jorgensen's asymmetric epoxidation of aldehydes for the introduction of chirality makes this approach more attractive. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: alpha-Aminooxylation; Jorgensens's asymmetric epoxidation; Macrolide; Ring-closing metathesis; Total synthesis

Efficient Sn(II)-catalyzed one-pot synthesis of a 3-substituted azetidine-2,4-dione framework - Chavan, Santosh S.; Supekar, Mrudul V.; Burate, Pralhad A.; Rupanwar, Bapurao D.; Shelke, Anil M.; Suryavanshi, Gurunath (Organic & Biomolecular Chemistry, 2017)
A novel Sn(II)-catalyzed tandem cyclization reaction of aromatic aldehydes with ethyl cyanoacetate has been achieved to afford a series of 3-substituted azetidine-2,4-diones in good to excellent yields. This protocol provides straightforward access to construct the azetidine core through sequential Knoevenagel condensation, hydration and the C-N cyclization reaction.

Enantioselective synthesis of (+)-Sedridine, (-)-Allosedridine and their N-Methyl analogs via Maruoka-Keck allylation and CBS reduction - Bhoite, Shubhangi P.; Suryavanshi, Gurunath (Natural Product Research, 2023)
A simple synthetic approach has been developed for the enantioselective total synthesis of (+)-Sedridine, (-)-Allosedridine and their analogs such as (+)-N- Methyl Sedridine and (-)-N-Methylallosedridine. The synthesis was achieved by using commercially available starting materials via Maruoka-Keck allylation, Wacker oxidation, and CBS reduction. The synthetic root provides a good diastereomeric ratio and high yields.
Keywords: CBS reduction; Maruoka-Keck allylation; Piperidine; Wacker oxidation